(untitled) (Journal of Hama University, 2019)
The Present study was designed to evaluate the effect of xylazine 2% on some elements and Biochemical of Dogs blood and record some vital reflexes (Heart rate ,analgesic, absence of sensory reflexes ,Respiratory rate and body temperature) which appear in dogs during injection and after injection. For this Purpose ,six local breed dogs of about 6-8 kg body weight(male) and Aged between 2-4 years where blood samples were taken before injection then all dogs were injected intravenously with xylazine 2%. After that blood samples were taken after 15,30,60,120 minutes and after 24 hours. Then sensory reflexes are recorded according to previous intervals. As a result , heart rate ,respiratory rate and body temperature showed significant decrease (P<0.05) at time 15,30 and 60 minutes. Hemoglobin ,PCV, blood platelets and Red Blood Cells were showed a significant decrease (P<0.05) after injection of xylazine 0,25 mgat time 30,60 minutes while, White blood cells were not showed any changes .There were significant increase (P<0.05) in serum enzymatic activities of (ALT,AST, CPK, ALP , GGT) at time 30 minutes after administration, Creatinine, and Glucose showed a significant increase at time 15,30,60 minutes after injection, whereas Albumin, Magnesium and Potassium showed a significant decrease (P<0.05) at time of 15.30,60 minutes whereas Sodium at time of 30 minutes.